2005
DOI: 10.1016/j.wasman.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fugitive bioaerosol releases from static compost windrows: Feasibility of a portable wind tunnel approach

Abstract: An assessment of the fugitive release of bioaerosols from static compost piles was conducted at a green waste composting facility in South East England; this representing the initial stage of a programme of research into the influence of process parameters on bioaerosol emission flux. Wind tunnel experiments conducted on the surface of static windrows generated specific bioaerosol emission rates (SBER2s) at ground level of between 13 and 22 x 10(3) cfu/m2/s for mesophilic actinomycetes and between 8 and 11 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 2 publications
0
40
0
3
Order By: Relevance
“…In our study, the airborne heterotroph concentration was 8-fold higher at DW2 than the upwind site, but it was determined that these were statistically similar concentrations. Research on the land application of biosolids or at composting facilities has shown that bioaerosol concentrations decrease with increasing distance from the source (Brooks et al 2004;Taha et al 2005). Similarly, decreases in bioaerosol concentrations with increasing distance from wastewater treatment plants and land application of wastewater have been demonstrated (Brooks et al 2004;Millner 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the airborne heterotroph concentration was 8-fold higher at DW2 than the upwind site, but it was determined that these were statistically similar concentrations. Research on the land application of biosolids or at composting facilities has shown that bioaerosol concentrations decrease with increasing distance from the source (Brooks et al 2004;Taha et al 2005). Similarly, decreases in bioaerosol concentrations with increasing distance from wastewater treatment plants and land application of wastewater have been demonstrated (Brooks et al 2004;Millner 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found A. fumigatus spore concentrations close to compost piles sometimes exceeded 10 6 cfu m -3 (Clark et al 1983). Elevated levels of A. fumigatus between 57.8 · 10 3 and 111.3 · 10 3 cfu m -3 were observed up to 30 m away from the compost (Taha et al 2005). Syzdek and Haines (1995) found mean daily A. fumigatus concentrations were much higher 30 m from the compost facility (552 spores m -3 ) than at either the local community site (151 spores m -3 ) 540 m downwind of the facility or the control site (44 spores m -3 ) 10,000 m upwind of the composting facility.…”
Section: Introductionmentioning
confidence: 93%
“…One that has been performed showed that on-site concentrations of fungal spores, viable bacteria and viable fungi were, not unexpectedly, higher compared to those monitored off-site. Furthermore the bioaerosol levels were measured to be higher during composting agitation processes as opposed to when there was no activity and that the concentrations exhibited a tendency to decrease with downwind distance (Taha et al, 2005(Taha et al, , 2006Hryhorczuk et al, 2001).…”
Section: Introductionmentioning
confidence: 99%